1992
DOI: 10.3171/jns.1992.76.5.0772
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparison of intra-arterial versus intravenous with or without intravenous 5-fluorouracil, for newly diagnosed patients with malignant glioma

Abstract: This Phase III trial tested the efficacy and safety of intra-arterial 1,3-bis(2-chloroethyl)-1-nitrosourea (BCNU) for the treatment of newly resected malignant glioma, comparing intra-arterial BCNU and intravenous BCNU (200 mg/sq m every 8 weeks), each regimen without or with intravenous 5-fluorouracil (1 gm/sq m three times daily given 2 weeks after BCNU). All patients also received radiation therapy. A total of 505 patients were randomly assigned within the study. Fifty-seven patients were excluded, primaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
84
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(87 citation statements)
references
References 43 publications
3
84
0
Order By: Relevance
“…5-Fluorouracil (5-FU) a pyrimidine analog, is one of the broad spectrum anticancer drugs [3][4][5] used in the treatment of malignancies like glioblastoma 6 and breast cancer. 7 Since 5-FU interferes with DNA synthesis, it principally acts as a thymidylate synthase inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…5-Fluorouracil (5-FU) a pyrimidine analog, is one of the broad spectrum anticancer drugs [3][4][5] used in the treatment of malignancies like glioblastoma 6 and breast cancer. 7 Since 5-FU interferes with DNA synthesis, it principally acts as a thymidylate synthase inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…Neuro-Oncology 5, 79-88, 2003(Posted to Neuro-Oncology [serial online], Doc. 02-023, February 10, 2003 P resently, malignant gliomas are treated by resection, external beam radiation, and, in some cases, systemic chemotherapy (Cairncross et al, 1992;Chang and Prados, 1995;Cristante et al, 1992;Fine et al, 1993;Hildebrand et al, 1997;Lesser and Grossman, 1994;Reulen et al, 1988;Shapiro et al, 1992;Walker et al, 1980). Randomized trials of radiotherapy have consistently shown an improvement in survival compared to surgery alone (Walker et al, 1980).…”
mentioning
confidence: 99%
“…The route of chemotherapy administration was assessed in the BTSG trial 8301 (Shapiro et al, 1992). Patients with newly resected malignant glioma received either intra-carotid BCNU or intravenous BCNU with or without intravenous 5-fluorouracil (5-FU).…”
mentioning
confidence: 99%